Epidemiological and clinical features, response to HAART, and survival in HIV-infected patients diagnosed at the age of 50 or more - Nogueras, MaMercedes (BioMed Central, 2006)
BACKGROUND: Over the last years, the mean age of subjects with HIV infection and AIDS is increasing. Moreover, some epidemiological and clinical differences between younger and older HIV-infected individuals have been observed. However, since introduction of HAART therapy, there are controversial results regarding their response to HAART. The aim of the present study is to evaluate epidemiological and clinical features, response to HAART, and survival in elderly HIV-infected patients with regard to younger HIV-infected patients. METHODS: A prospective cohort study (1998–2003) was performed on patients from Sabadell Hospital, in Northeast of Spain. The cohort includes newly attended HIV-infected patients since January 1, 1998. For the purpose of this analysis, data was censured at December 31, 2003. Taking into account age at time of diagnosis, it was considered 36 HIV-positive people aged 50 years or more (Group 1, G1) and 419 HIV-positive people aged 13–40 years (Group 2, G2). Epidemiological, clinical, biological and therapy data are recorded. Statistical analysis was performed using Chi-squared test and Fisher exact test, Mann-Whitney U test, Kaplan-Meier, Log Rank test, and Two-Way ANOVA from random factors. RESULTS: G1 showed higher proportion of men than G2. The most common risk factors in G1 were heterosexual transmission (P = 0.01) and having sex with men or women (P < 0.001). G1 and G2 show parallel profiles through the time regarding immunological response (P = 0.989) and virological response (P = 0.074). However, older people showed lower CD4 cell counts at first clinic visit (P < 0.001) and, eventually, they did not achieve the same counts as G2. G1 presented faster progression to AIDS (P < 0.001) and shorter survival (P < 0.001). CONCLUSION: Older patients have different epidemiological features. Their immunological and virological responses are good. However, older patients do not achieve the same CD4 cell counts likely due to they have lower counts at first clinic visit. Thus, it is essential physicians know older HIV-infected patients features to consider the possibility of HIV infection in these patients with the aim of treatment would not be delayed.